EMPOWERMENT OF PKK CADRES THROUGH TRAINING ON PROCESSING COCOMIXS WASTE INTO LIQUID ORGANIC FERTILIZER (PCO-YOCOCO) TO SUPPORT THE SUSTAINABILITY OF THE RAHAYU GARDEN IN TEGUHAN VILLAGE - Qurrotul Anfa; Ratna Tri Widyawati; Lina Rumiati; Desi Nuzul Agnafia (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2025)
This community service program aimed to empower PKK (Family Welfare and Empowerment) women cadres in Teguhan Village through the utilization of organic waste to support sustainable agriculture and local economic resilience. Specifically, the program focused on training cadres to process coconut husk waste from Cocomixs beverage production and leftover household rice into an organic liquid fertilizer named PCO-Yococo. The program employed a Participatory Action Research (PAR) approach, emphasizing active community involvement throughout the process. Activities were implemented in five stages: planning, socialization, training, technical guidance, and mentoring. The methods included environmental observation, participatory formulation of PCO-Yococo production procedures, hands-on production practice, dissemination of a digital pocket book, and periodic monitoring of the fermentation process and plant growth in Kebun Rahayu. The results showed significant improvements in participants’ technical skills related to organic fertilizer production, increased production capacity, and enhanced social and economic empowerment among PKK cadres. Overall, this program indicates that a participatory, community-based waste management initiative can effectively transform local waste into value-added agricultural inputs while strengthening environmental awareness, social capacity, and economic resilience in Teguhan Village.